Implementasi Kurikulum Merdeka pada Tingkat Satuan Pendidikan SMA: Tinjauan Perencanaan IKM - Fitri, Rahmadhani; Rurisman; Gistituati, Nurhizrah; Bentri, Alwen (Pedagogi Hayati, 2022)
Due to the Covid-19 pandemic, education in Indonesia needs to make adjustments so that the implementation of education can continue. One of the policies carried out by the government under the auspices of the Ministry of Education and Culture was to implement the Emergency Curriculum (simplified Curriculum-2013). Over time, the government prepared a new curriculum prototype which has now been formalized as the Independent Curriculum. The implementation of the Independent Curriculum (IKM) begins in stages in schools called “Sekolah Penggerak”. This research was conducted to find out how the planning and design stages of IKM were carried out by a Sekolah Penggerak in one of the schools in West Sumatra. Data obtained from observations and interviews conducted with informants who know and are involved in IKM. Based on the results of the research that has been done, it was found that the initial step taken by the school as a driving school was to form a Curriculum Development Team (TPK) which would later coordinate with the provincial TPK. Some of the activities that have been carried out by TPK schools were observed. The preparations that have been made to become a driving school are (1) conducting training for teachers, (2) forming a learning committee, (3) compiling the Curriculum of Education Unit Operational (KOSP), (4) preparing curriculum tools such as KSOP, Outcomes Learning (CP), Learning Objective Flow (ATP), teaching modules, and strategies for implementing project-based learning or projects to strengthen the profile of Pancasila students. Apart from that, the things that schools have prepared in facing an independent curriculum are (1) studying and understanding the regulations regarding an independent curriculum, (2) coordinating with all teacher boards, and 3) adopting a level of complexity curriculum.